2020
DOI: 10.21203/rs.3.rs-34122/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular detection of Blastocystis from animals in Italy: subtypes distribution and implications for the zoonotic transmission

Abstract: Background: Blastocystis is a common intestinal protist distributed worldwide infecting humans and a wide range of domestic and wild animals. It exhibits an extensive genetic diversity and so far, 26 subtypes (STs) have been identified in animal hosts, ten of them (ST1-ST9 and ST12) reported in humans with varying prevalence. Since several STs are common to humans and animals it has been proposed that a proportion of human infections may have a zoonotic origin. Aims of the present study were to: 1) genetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…ST5 allele 16 was the most commonly encountered in pigs and ST allele 2 was the most commonly encountered in macaques. In comparison, ST5 allele 115 was the most commonly encountered in pigs from Italy [ 92 ] and ST1 allele 2 was the most commonly identified in long-tailed macaques from Thailand [ 72 ]. Not much data on allele distribution is available for animals and water samples.…”
Section: Discussionmentioning
confidence: 99%
“…ST5 allele 16 was the most commonly encountered in pigs and ST allele 2 was the most commonly encountered in macaques. In comparison, ST5 allele 115 was the most commonly encountered in pigs from Italy [ 92 ] and ST1 allele 2 was the most commonly identified in long-tailed macaques from Thailand [ 72 ]. Not much data on allele distribution is available for animals and water samples.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Blastocystis varies significantly depending on geographical location and host type (Ruaux and Stang 2014). In studies conducted on cattle, the prevalence was reported as 21.4% in Brazil (Moura et al 2018), 22.7% in Arabia (Abuodeh et al 2019), 32.1% in Spain (Abarca et al 2021, 10.3% in China (Zhu et al 2017), 6.7% in Korea (Lee et al 2018, 80% in Colombia (Ramírez et al 2014), 34.5% and 43.8% in Malaysia (Hemalatha et al 2014, Kamaruddin et al 2020, 71% in Japan (Abe et al 2002) and 33% in calves in Italy (Gabrielli et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…shows a wide genetic diversity. It has been reported that 26 subtypes (ST) have been defined in animals so far and ST10 is the most common subtype in cattle in the world (Aynur et al 2019, Gabrielli et al 2020. It was reported that two subtypes, ST10 and ST14, were detected in cattle in the southwest of Turkey and ST14 was more common (Aynur et al 2019), ST10 was detected in cattle and sheep in the Central Anatolia and Central Black Sea Region (Onder et al 2021), and in a different study conducted also in the Central Anatolia Region, the ST10 subtype was determined in cattle (Tavur and Önder 2022).…”
Section: Discussionmentioning
confidence: 99%